Hotel Customer Perspectives Through the Customer Journey on Omnichannel Marketing in 4.0 Era - Utami, Ketut Aryati; Darma, Gede Sri (Universitas Hamzanwadi, 2024)
The emergence of digitalization and technology has led consumers to utilize various channels and service providers for their purchases. It is undeniable that the market is increasingly shifting towards online channels, creating a hybrid situation where some products exist in an omni-channel environment. This situation gives rise to unique phenomena in the industrial world, which subsequently question the presence and relevance of offline channels in promoting and selling products/services in a company. This research aims to deeply explore how hotel customers' perspectives are viewed from the customer journey in omnichannel marketing in the era of 4.0. This study utilizes primary and secondary data. Primary data is collected through direct interviews with informants. Semi-structured in-depth interviews are conducted with 4 hotel customers from the four largest market segments of the hotel. The research results reveal the stages of the hotel customer journey in an omni-channel environment, from the initial stage to the end.